41.5: Head‐mounted Display Based on Surface Relief Grating for Augmented Reality. (28th November 2018) - Ding, Wuwen; Zheng, Yu
Abstract : A see‐through head‐mounted display (HMD) is demonstrated in the paper, which can present the user with information such as virtual symbols or images superimposed over real‐world image. To meet the human eyes' visual requirements under different situations, a large exit pupil of 2 to 5 times of the pupil size (about 2.4 mm) is required. To solve the problem, the HMD presented in the paper is a combination of micro‐display of LCoS, imaging eyepiece and an exit pupil expander based on planar waveguide with slanted surface relief grating. Both transmission and reflection gratings are applied in the HMD design. Two system schemes are presented which expand the light only along one direction and two orthogonal directions, respectively. The system configuration and principle of operation are described in the paper.